THE POTENTIAL USE OF ACACIA LEAF MEAL AS PROTEIN FEED SOURCE FOR POULTRY DIETS: A REVIEW - S. D. Kolobe; J. W. Ng’ambi; T. Chitura; E. Malematja; M. F.D. Nemauluma; T. G. Manyelo (Journal of Animal and Plant Sciences, 2022)
Poultry accounts for more than 30 % of all animal protein consumption worldwide. It is estimated that by 2030, poultry will account for 41 % of all animal protein consumed by people due to low income and population growth. Protein feed sources are considered the most valuable but expensive ingredients in poultry production. High feed cost is the major problem faced by livestock and poultry farmers, especially those in rural communities. The need to search for alternative feed sources has triggered much interest in the use of Acacia meals including A. karroo, A. tortilis, A. nilotica, and A. angustissima leaf meals in poultry diets since they are readily available, grow in abundance, and cover large areas in most parts of Africa. Acacia meals have high nutritional values due to their large amounts of crude protein, hence, can effectively serve as an alternative protein feed source for the poultry diet. However, their utilisation is restricted by the presence of tannins within the leaves. Previous research on the inclusion of Acacia meals in poultry species focused mainly on broiler chicken diets. Therefore, the present review encompases the potential use of Acacia meal as a cheap and alternative protein source in poultry diets.
Keywords: Acacia meal; Tannins; Protein feed source; Poultry